Analisis Evaluasi Penerapan Pemungutan Pajak Air Tanah Dalam Upaya Peningkatan Pendapatan Pajak Air Tanah Di BAPENDA Kota Bekasi (Studi Kasus BAPENDA Kota Bekasi) - Maria Magdalena Ika; Dian Wahyudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study was conducted to determine the analysis of the application of groundwater tax collection as an effort to increase groundwater tax revenue in the BAPENDA (Regional Revenue Agency) of Bekasi City, the obstacles that arise in the groundwater tax collection and the efforts made to overcome them. This study used a descriptive qualitative research method. Data was collected through interviews, observation and documentation. The results of the study show that data collection and monitoring of groundwater tax collection as an effort to increase groundwater tax revenue at the BAPENDA of Bekasi City is practically in accordance with Law No. 28 of 2009 and regulations regarding groundwater tax. However, the ineffectiveness of the tax collection system and the lack of maximum groundwater tax services have made groundwater tax collection at the BAPENDA of Bekasi City less than optimal.